Extracorporeal shock wave treatment protects skin flaps against ischemia-reperfusion injury - Reichenberger, Matthias; Heimer, Sina Franziska; Schaefer, Amelia; Gebhard, Martha-Maria; Germann, Günter; Engel, Holger; Köllensperger, Eva; Leimer, Uwe; Müller, Wolf C. (Injury, 2012)
Advances in the treatment of ischemia-reperfusion injury have created an opportunity for plastic surgeons to apply these treatments to flaps and implanted tissues. Using an extended inferior epigastric artery skin flap as a flap ischemia-reperfusion injury (IRI) model, we examined the capability of extracorporeal shock wave treatment (ESWT) to protect tissue against IRI in a rat flap model. Twenty-four rats were used and randomly divided into three groups (n=8 for each group). Group I was the sham group and did not undergo ischemic insult; rather, the flap was raised and immediately sutured back (non-ischemic control group). Group II (ischemia control) and Group III (ESWT) underwent 3h of ischemic insult. During reperfusion Group III was treated with ESWT and Group II was left untreated. Histological evaluation was made to investigate treatment induced tissue alterations. Survival areas were assessed at 5d postoperatively. Skin flap survival and perfusion improved significantly in the ischemic animals following ESWT (p<0.001, respectively). The tissue protecting effect of ESWT resulted in flap survival areas and perfusion data equal to non-ischemic, sham operated flaps. In line with the observation of better flap perfusion, tissue from ESWT-treated animals (Group III) revealed a significantly increased frequency of CD31-positive vessels compared to both the ischemic (Group II; p=0.003) and the non-ischemic, sham operated control (Group I; p<0.005) and an enhanced expression of pro-angiogenic genes. This was accompanied by a mild suppression of pro-inflammatory genes. Our study suggests that ESWT improves flap survival in IRI by promoting angiogenesis and inhibiting tissue inflammation. The study identifies ESWT as a low-cost and easy to use technique for surgical techniques that aim at reducing ischemia-reperfusion-induced tissue injury